Evaluation of initial material for the obtaining of high-amylose rice - Usenbekov, B.N.; Amirova, А.К.; Berkimbay, Kh.A.; Zhanbyrbayev, Е.А.; Kazkeev, D.T.; Zhaisankulova, U.B.; Sartbayeva, I.A. (Fundamental and Experimental Biology, 2022)
Rice is one of the main crops of strategic importance. Rice consumption in Kazakhstan is increasing compared to other cereals and reaches more than 65 %. Today, due to the increase in imports of rice cereals, it seems relevant to develop rice production, increase its competitiveness, and create domestic rice varieties with improved nutritional and culinary qualities. Akey factor in determining the quality of rice is the percentage of amylose in the starch of the rice grain. In this regard, this work is devoted to the search for donors of the trait “high amylose content” among varieties and lines of domestic and foreign breeding in the rice collection of the RSE on the REM “Institute of Plant Biology and Biotechnology” (RSE on the REM “IPBB”). Screening of 172 foreign and domestic varieties and lines of rice for amylose content made it possible to identify 9 high-amylose variety samples. Among them one domestic ancient variety of Kazakh selection K3077 Kazakhi was found, which can serve as a donor of the trait “high amylose content”. Because of the climatic conditions of Kazakhstan and the long growing season, only six foreign varieties and lines were selected: Mavr (26.8 %), Taibonet (25.4 %), Parity (27, 0 %), K3612 Kara-Kyltyk (25.0 %), K3077 Kazakhs (25.1 %), and Solnechny (25.4 %). The selected varieties and lines of rice with a high contentof amylose will be used as donors of the “high amylosecontent” trait for rice breeding.